Green SrSi2O2N2:Eu2+ phosphor for LED-phosphor applications: synthesis and characterization - Ha Thanh Tung; My Hanh Nguyen Thi (Institute of Advanced Engineering and Science, 2023)
Green phosphors SrSi2O2N2:Eu2+ (SSON:Eu) are combined utilizing a simple solid-state reaction with SrSi2O2N2:Eu2+ like the forerunner. Various phosphor attributes were assessed following creation procedure. Differential thermal analysis (DTA) spectra and luminescence measurements are used to assess crystalline active power, electron-phonon conjunction, and heat quenching behavior. Because of their poor electron-phonon conjunction intensity (Huang-Rhys factor=4.2), SSON:Eu green phosphors have outstanding heating and color consistency. The heat quenching temperature (T50) of SSON:Eu is greater than 200 °C. SSON:Eu green phosphors have a wide stimulation range, strong heat steadiness and can absorb ultraviolet (UV) to blue energy and release green illumination, leading to the appropriate utilization in solid-state illumination and GaAsAl solar cells, according to the findings.